2017
DOI: 10.1007/s00401-017-1737-3
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of TYROBP, an adapter protein for TREM2 and CR3 receptors, is neuroprotective in a mouse model of early Alzheimer’s pathology

Abstract: Conventional genetic approaches and computational strategies have converged on immune-inflammatory pathways as key events in the pathogenesis of late onset sporadic Alzheimer’s disease (LOAD). Mutations and/or differential expression of microglial specific receptors such as TREM2, CD33, and CR3 have been associated with strong increased risk for developing Alzheimer’s disease (AD). DAP12 (DNAX-activating protein 12)/TYROBP, a molecule localized to microglia, is a direct partner/adapter for TREM2, CD33, and CR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 87 publications
17
98
0
Order By: Relevance
“…In the present study, three cases of NHD showed the homozygous mutation of c.141delG in exon 3 of DAP12. A recent study showed that deficiency of DAP12 does not modify the number and size of Aβ plaque deposition in the prefrontal cortex and the hippocampus of APP/PSEN1 mice, although DAP12 deficiency reduces plaque compaction, microglial clustering, and phagocytosis (20). Furthermore, phosphorylation of tau is attenuated in female APP/ PSEN1 mice with loss of DAP12.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, three cases of NHD showed the homozygous mutation of c.141delG in exon 3 of DAP12. A recent study showed that deficiency of DAP12 does not modify the number and size of Aβ plaque deposition in the prefrontal cortex and the hippocampus of APP/PSEN1 mice, although DAP12 deficiency reduces plaque compaction, microglial clustering, and phagocytosis (20). Furthermore, phosphorylation of tau is attenuated in female APP/ PSEN1 mice with loss of DAP12.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of TREM2 in a tau mouse model led to less brain atrophy. Interestingly, deficiency of TYROBP, the adapter protein for TREM2, was neuroprotective in a mouse model of AD (Haure‐Mirande et al, ). The deficiency of TYROBP resulted in an altered expression of AD‐related genes, with less severe neuritic dystrophy and attenuated learning behavior deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Genes relating to TYROBP signaling, which is implicated in Alzheimer's and regulates phagocytosis, cell proliferation, activation and survival, were significantly upregulated (Keren-Shaul et al, 2017;Landreth & Reed-Geaghan, 2009;Ma et al, 2015). Substantiating these findings Tyrobp knockout mice models have proven to suppress inflammation in neurodegenerative models including Alzheimer's, thereby minimizing neuronal dystrophy, implicating a failure in the resolution of inflammation in Alzheimer's(Bakker et al, 2000;Haure-Mirande et al, 2017). Interestingly mutations and expression of downstream members are also linked with…”
mentioning
confidence: 99%